Marketing Mix to Improve the Family Economy of Female Silk Craftsmen in Tanasitolo District, Wajo Regency - Muh. Akbar; Syahriyah Semaun; An Ras Try Astuti; St. Aminah; Damirah Damirah (Jurnal Ekonomi Balance, 2025)
This study investigates the role of the marketing mix strategy in strengthening the family economy of female silk weavers in Tanasitolo District, Wajo Regency, from the perspective of Islamic economics. Employing a descriptive qualitative methodology with a phenomenological approach, this field research aims to explore how the implementation of the 7P marketing mix strategy—Product, Price, Place, Promotion, People, Process, and Physical Evidence—contributes to business sustainability and household welfare among women-led silk weaving enterprises. Primary data were obtained through in-depth interviews with female silk weavers, while secondary data were sourced from relevant literature, including books and peer-reviewed journal articles. The findings indicate that the effective application of the 7P marketing mix, when aligned with Islamic economic principles such as fairness, honesty, and mutual benefit, enhances product competitiveness, improves market access, increases sales performance, and ultimately strengthens family economic resilience. Furthermore, the integration of ethical values derived from Islamic economics supports sustainable business practices and empowers women as key economic actors within their households and communities. This study offers practical implications for policymakers, development practitioners, and micro-entrepreneurs by highlighting the importance of integrating strategic marketing approaches with Islamic economic values to promote inclusive economic development and improve the welfare of female micro-entrepreneurs.